Stomach cancer risk factors: the modern concept - V. M. Khomyakov; A. D. Yermoshina; S. S. Pirogov; A. B. Ryabov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To present the systematic overview of the stomach cancer risk factors to determine prophylactic measures and to define high-risk groups of population that can be included to the screening programs. Summary. Stomach cancer (SC) represents one of the leading causes for morbidity and mortality among malignant neoplasms worldwide. SC is asymptomatic at early stages that causes higher rate of locally advanced and disseminated forms of the tumor at primary diagnosis. SC early detection screening programs demonstrated high efficacy only in the Asian region. The main role in early detection of this disease is played by oncological alertness of doctors at outpatient clinics and gastroenterologists, as well as the patient education. The understanding of basic etiologic and predisposing factors and mechanisms of SC development, knowledge of key risk factors allow to distinguish high-risk groups from the general population and to carry out active revealing of premalignant lesions and early forms of SC. Conclusion. Stomach cancer is a multifactorial disease which develops under effect and interaction of external and internal factors. Intestinal type SC and diffuse type SC have various pathogenesis and risk factors. Risk factor estimation provides effective prophylaxis of the disease, and also to reveal high risk groups for preventive and screening programs.